Rancang Bangun Sistem Penguncian Pintu Menggunakan Sensor Fingerprint Berbasis NodeMCU ESP8266 (Studi Kasus: Lab Komputer SMK Grafika Yayasan Lektur) - Alfian Pratama Putra; Maulana Ardhiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The computer lab door finishing system is an important component in maintaining security and managing access to the computer lab room in schools. Automatic door locking has become a technology that is increasingly popular in various environments, such as homes, offices and public facilities. To increase the security and convenience of using automatic doors, the use of fingerprint recognition has become an interesting approach. This study aims to develop and implement an automatic door locking system using fingerprint technology. In this abstract, we introduce a solution that combines fingerprint technology (fingerprint) and the NodeMCU ESP8266 module to create a secure, efficient and easy-to-use door display system. This system utilizes the NodeMCU ESP8266 module as a microcontroller platform to control the door management mechanism automatically. This module is equipped with WiFi capability, so it can be connected to a local network or the internet. Fingerprint is used as a user authentication method which is integrated with the fingerprint sensor connected to the NodeMCU ESP8266. In its implementation, this system has several advantages. First, the use of fingerprint technology provides a high level of security, because a fingerprint is a unique identity that is difficult to fake. Second, integration with the NodeMCU ESP8266 module allows the system to be connected to a local network or the internet, so that it can be controlled remotely and allows administrators to easily manage user access. Third, these systems can be implemented at relatively low cost and using commercially available hardware. In this study, we tested the computer lab door delivery system using a fingerprint and the NodeMCU ESP8266 module. The test results show that the system can recognize fingerprints with high accuracy and provides a fast response when opening or locking the door. Thus, the proposed computer lab door construction system has great potential to improve security and manage access to computer lab rooms in schools efficiently. Further development can be done to extend the functionality of the system, such as integration with more complex access management systems.